Towns and townspeople of Central Poland and the Teutonic invasion in 1331 - Ćwikła, Łukasz (City and War, 2021)
In 1331 Władysław Łokietek was at war with the Teutonic Order, which filled the last years of his reign. During the Teutonic invasions many towns, villages, local people, forts, churches and monasteries suffered. The next ruler, i.e. Kazimierz Wielki, decided to open the lawsuit against the Teutonic Knights in order to regain the lost lands, Gdańsk Pomerania, the lands of Chełmno, Dobrzyń, the castellany of Michałów and Kujawy. Extensive procedural documentation can be found in the source publication Lites ac res gestae inter Polonos Ordinemque Cruciferorum. In addition to the princes, knights and clergy, testimony against specific articles was also made by the townspeople who actively participated in the trial. They testified to the aggression of the Teutonic Knights, which they experienced many times, emphasizing not only direct harm, but also the destruction of cities and church property. By analyzing individual testimonies, you can try to capture specific material losses during the turmoil of war. This text is also a contribution to further research on the participation of the townspeople in the Polish-Teutonic trial.